2014
DOI: 10.3109/14397595.2014.942503
|View full text |Cite
|
Sign up to set email alerts
|

Clinical features and pregnancy outcome in antiphospholipid syndrome patients with history of severe pregnancy complications

Abstract: Objective. To clarify the clinical significance of antiphospholipid antibody (aPL) profile in patients with obstetric antiphospholipid syndrome (APS). Methods. Clinical records of 13 pregnant patients (15 pregnancies) with obstetrical APS were reviewed over 10 years. Patients who met the Sapporo Criteria fully were studied, whereas those with only early pregnancy loss were excluded. In addition to classical aPL: lupus anticoagulant (LA), anticardiolipin antibody (aCL), and anti-β2-glycoprotein I (aβ2GPI); phos… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 15 publications
(7 citation statements)
references
References 12 publications
0
7
0
Order By: Relevance
“…Although it is indeed true that the treatment of a pregnant APS patient should depend on the level of her obstetric risk, it is not yet clear how maternal-fetal risk of pregnancy complications should be calculated. Several studies have shown that some specific aPL profiles in APS patients are linked to a high risk of poor pregnancy outcome or to being refractory to conventional therapy [125][126][127][128][129]. These profiles include multiple aPL positivity [125] and, in particular, contemporaneous positivity to all three aPL assays (119; 120), lupus anticoagulant activity [128], and high aPL titres [129].…”
Section: Intravenous Immunoglobulins and Plasma Exchange Alone Or Com...mentioning
confidence: 99%
See 1 more Smart Citation
“…Although it is indeed true that the treatment of a pregnant APS patient should depend on the level of her obstetric risk, it is not yet clear how maternal-fetal risk of pregnancy complications should be calculated. Several studies have shown that some specific aPL profiles in APS patients are linked to a high risk of poor pregnancy outcome or to being refractory to conventional therapy [125][126][127][128][129]. These profiles include multiple aPL positivity [125] and, in particular, contemporaneous positivity to all three aPL assays (119; 120), lupus anticoagulant activity [128], and high aPL titres [129].…”
Section: Intravenous Immunoglobulins and Plasma Exchange Alone Or Com...mentioning
confidence: 99%
“…Several studies have shown that some specific aPL profiles in APS patients are linked to a high risk of poor pregnancy outcome or to being refractory to conventional therapy [125][126][127][128][129]. These profiles include multiple aPL positivity [125] and, in particular, contemporaneous positivity to all three aPL assays (119; 120), lupus anticoagulant activity [128], and high aPL titres [129].…”
Section: Intravenous Immunoglobulins and Plasma Exchange Alone Or Com...mentioning
confidence: 99%
“…Some investigators found a higher risk of maternal and foetal complications in pregnant APS women with previous thromboembolism [38], and others reported the association of pregnancy loss with the presence of multiple antiphospholipid positivity, i.e., for anti-β2GPI antibodies and LAC [39,40]. A history of thrombosis [41,42], some particular antiphospholipid antibody profiles such as the presence of LAC [43] or high titres of aCL or anti-β2GPI antibodies [44] and APS associated with systemic lupus erythematosus or other systemic autoimmune diseases [43,45] have been found to be related to maternal-foetal complications in pregnant APS women.…”
Section: High-risk Obstetric Apsmentioning
confidence: 99%
“…Moreover, the presence of persistent positive LA [74,75] has been reported as the strongest predictor for either pregnancy loss or recurrent thrombosis. These high-risk aPL profiles (Table 2) are associated with an increased risk of pregnancy morbidity such as intrauterine growth restriction and premature birth as well as pre-eclampsia despite appropriate anticoagulant treatment [73,[76][77][78]. Regarding clinical features, women with aPLs and a history of thrombosis, severe pregnancy complications such as pre-eclampsia, eclampsia, or HELLP syndrome, a concomitant SLE diagnosis, or low complement levels are associated with a higher risk of pregnancy morbidity [78,79].…”
Section: Risk Stratification In Obstetric Antiphospholipid Syndromementioning
confidence: 99%